VOCABULARY MASTERY WITH STORYTELLING METHODS AND CONVENTIONALITY STRATEGIES AND REFERENCES TO STUDENTS IN THE A1 TK RAHMA CIRACAS - Endang Sulistijani (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
Abstract:. Teaching languages in early childhood (3-5 years of age) requires a fun method. In early childhood it is commonly referred to as The Golden Age. Stories need to be given to children considering the many benefits that can be obtained from a story. Besides giving pleasure and presenting various experiences and insights for children, stories are thought to be able to improve children's language skills. This study aims to describe the process of mastering the vocabulary of children through the method of telling stories with conventionality and reference strategies for A1 grade students at TK Rahma Ciracas. The research method used is descriptive qualitative with observation, interviews, and recording results. With conventional strategies and references, mastery of vocabulary in children is more focused and directed, so mistakes in determining their meaning can be avoided. In addition, the method of telling stories with this strategy is very effective for language teaching in early childhood.